Accumbal adenosine A2A receptor inactivation biases for large and costly rewards in the effort- but not delay-based decision making. (1st January 2023) - Sun, Xiaoting; Liu, Min; Xu, Xinyu; Shi, Chennan; Zhang, Liping; Yao, Zhimo; Chen, Jiangfan; Wang, Qin
Abstract: The cost-benefit decision-making (CBDM) is critical to normal human activity and a diminished willingness to expend effort to obtain rewards is a prevalent/noted characteristic of neuropsychiatric disorders such as schizophrenia, Parkinson's disease. Numerous studies have identified nucleus accumbens (NAc) as an important locus for CBDM control but their neuromodulatory and behavioral mechanisms remain largely under-explored. Adenosine A2A receptors (A2A Rs), which are highly concentrated in the striatopallidal neurons, can integrate glutamate and dopamine signals for controlling effort-related choice behaviors. While the involvement of A2A Rs in effort-based decision making is well documented, the role of other decision variables (reward discrimination) in effort-based decision making and the role of A2A R in delay-based decision making are less clear. In this study, we have developed a well-controlled CBDM behavioral paradigm to manipulate effort/cost and reward independently or in combination, allowing a dissection of four behavioral elements: effort-based CBDM (E-CBDM), delay-based CBDM (D-CBDM), reward discrimination (RD), effort discrimination (ED), and determined the effect of genetic knockdown (KD) of NAc A2A R on the four behavioral elements. We found that A2A R KD in NAc increased the choice for larger, more costly reward in the E-CBDM, but not D-CBDM. Furthermore, this high-effort/high-reward bias was attributable to the increased willingness to engage in effort but not the effect of discrimination of reward magnitude. Our findings substantiate an important role of the NAc A2A R in control of E-CBDM and support that pharmacologically targeting NAc A2A Rs would be a useful strategy for treating the aberrant effort-based decision making in neuropsychiatric disorders. Highlights: A distinct cost-benefit choice paradigm was developed under different conflicts. A2A R KD in NAc selectively altered effort- but not delay-based decision making. NAc A2A R-driven bias in E-CBDM was due to increased willingness to engage in effort. NAc A2A R-driven bias in E-CBDM may be driven by enhanced activational motivation.